Kejadian Hiperemisis Gravidarum Ditinjau dari Jarak Kehamilan dan Paritas - Oktavia, Lina (Universitas Aisyah Pringsewu, 2016)
This study was conducted to determine the distance relationship with the incidence of pregnancy and parity Hiperemisis Gravidarum. Results Of the 284 study respondents there were 33.8 who experienced hyperemia gravidarum and 66.2% of mothers who did not experience hyperemia gravidarum. 34.2 with a distance-risk pregnancies and 65.8% with a distance of pregnancies at risk. There are 55.3% with high parity and 44.7% with low parity. From the test results obtained statistically no pregnancy distance relationship with hiperemisis gravidarum with p value of 0.000 and no association with maternal parity hiperemisis gravidarum with p value 0,002. Conclusion No relationship spaced pregnancies and maternal parity with hiperemisis gravidarum.Keywords: Distance Pregnancy, Parity, Hiperemisis Gravidarum